Pioneers in pathology and female role models: the Jewish scientists Rahel Rodler, Ruth Silberberg, Lotte Strauss and Zelma Wessely. Issue 4 (October 2022) - Uhlendahl, Hendrik; Kaiser, Stephanie; Biermanns, Nico; Groß, Dominik
Abstract: So far, female physicians have played a minor role in scientific studies of Nazi victims; this also applies to specialists in pathology. Against this background, the present study examines the biographies of the outstanding Jewish pathologists Rahel Rodler (1878–1944), Ruth Silberberg (1906–97), Lotte Strauss (1913–85) and Zelma Wessely (1914–2004). The focus is on their roles as women scientists and their fateful careers after the Nazi rise to power, embedded in the context of the position of women in medical studies and the medical profession of their time as well as in the subject of pathology. The study is primarily based on archival sources from various German, Austrian and Swiss state and university archives, from the British National Archives and from the National Archives and Records Administration in Washington DC. The paper provides three key findings: (1) The four female pathologists were rare exceptions in the contemporary pathological scientific community with a quantitative share of less than 5%. (2) They experienced discrimination on two levels (gender and 'race'). (3) Thanks to professional excellence and continued dedication, three of the four female pathologists were able to escape from Nazi Germany and achieve remarkable careers in emigration. It can be concluded that Rodler, Silberberg, Strauss and Wessely rose to female role models and pioneer scientists in contemporary pathology.